Ácidos graxos no desempenho e nas respostas imunológicas de bovinos Nelore confinados - Barducci, Robson Sfaciotti [UNESP]; Nave Sarti, Luis Marcelo [UNESP]; Millen, Danilo Domingues [UNESP]; Putarov, Thaila Cristina [UNESP]; Ribeiro, Felipe Azevedo [UNESP]; Silva Franzoi, Maria Caroline da [UNESP]; Costa, Carolina Floret da [UNESP]; Martins, Cyntia Ludovico [UNESP]; Arrigoni, Mario De Beni [UNESP] (Empresa Brasil Pesq Agropec, 2015)
The objective of this work was to evaluate the addition of natural and protected lipid sources on the performance and immune responses of Nelore cattle feedlot. A completely randomized design was carried out with repeated measures in time and three treatments, which were: without additional source of lipid (CONTR); with natural lipid source (cottonseed cake) (GDESP); and with rumen protected lipid source, rich in polyunsaturated fatty acids (GPROT). The study was divided into two phases: preconditioning and feedlot of 120 noncastrated Nelore cattle (24 pens, 5 animals per pen, and 8 pens per treatment). The GDESP treatment provided greater weight gain in the preconditioning phase, and, during the feedlot period, there were no differences among treatments for performance, carcass traits, and disease incidence. The highest plasma concentrations of TNF alpha, IL-1(beta), haptoglobin, and ceruloplasmin occurred in the CONTR treatment. Lipid supplementation to the diet, regardless of the source, improves the performance and enhances the immunological system of confined Nellore cattle.

O objetivo deste trabalho foi avaliar os efeitos da adição de fontes de lipídeos naturais e protegidos no desempenho e nas respostas imunológicas de bovinos Nelore em confinamento. Utilizou-se o delineamento experimental inteiramente casualizado com medidas repetidas no tempo e três tratamentos, que foram: sem fonte adicional de lipídeo (CONTR); com fonte de lipídeo natural (torta de algodão) (GDESP); e com fonte de lipídeo protegido e rico em ácidos graxos poli-insaturados (GPROT). O estudo foi dividido em duas fases: pré-condicionamento e confinamento de 120 bovinos Nelore inteiros (24 baias, 5 animais por baia e 8 repetições por tratamento). O tratamento GDESP proporcionou maior ganho de peso na fase de pré-condicionamento, e, durante o período de confinamento, não houve diferenças entre os tratamentos quanto ao desempenho, às características de carcaça e ao acometimento de enfermidades. As concentrações plasmáticas de TNFα, IL-1β, haptoglobina e ceruloplasmina foram superiores no tratamento CONTR. A adição de lipídeos à dieta, independentemente da fonte, promove melhora no desempenho e nos parâmetros imunológicos de bovinos Nelore confinados.
Fatty acids on the performance and immune responses of Nellore feedlot cattle
Keywords: Rumen protected fat; Preconditioning; Acute phase proteins; Pufa; Lipid suplementation; Gordura protegida; Pré-condicionamento; Proteínas de fase aguda; Pufa; Suplementação lipídica